Hippokrates i spalenie biblioteki - Wiszowata, Magdalena (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2014)
Hippocrates is presented in the sources as a valued and experienced doctor who devoted himself above all to the good of his patients, as well as a patriot who was concerned with the interests of the inhabitants of Greece and his native island Kos. This ideal image of a doctor, however, stirs up recollections of his burning down of the library on Kos. In my discussion of the question of H ippocrates’ connection with the library on Kos and in the medical centre in Knidos use is made of accounts of Hippocrates’ life which have been preserved until our times, written by Soranus of E phesus, namely: 1) Vita Hippocratis Secundum Soranum, an abbreviated version incorporated in the Corpus Hippocraticum; 2) a biography contained in the Chiliades of John Tzetzes, a Byzantine author from the 12th century, and also other available sources such as Pliny the Elder in the Natural History (29, 4, 1-12), as well as the Geography of Strabo (14, 2, 19).
Keywords: Hippocrates; Kos; library; asclepeion; Pliny the Elder; Soranus of Ephesus; Strabo